2019
DOI: 10.1016/j.bbmt.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Liver Stiffness Measurement Allows Early Diagnosis of Veno-Occlusive Disease/Sinusoidal Obstruction Syndrome in Adult Patients Who Undergo Hematopoietic Stem Cell Transplantation: Results from a Monocentric Prospective Study

Abstract: A B S T R A C T Veno-occlusive disease (VOD), also known as sinusoidal obstruction syndrome (SOS), is a life-threatening complication affecting patients undergoing hematopoietic stem cell transplantation (HSCT). The survival rate is higher when specific therapy is initiated early; thus, improving early, noninvasive diagnosis of VOD/SOS is an important need. In an adult population undergoing HSCT, we aimed to assess the role of liver stiffness measurement (LSM), evaluated by transient elastography (TE), for dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 44 publications
4
53
0
1
Order By: Relevance
“…In addition, Colecchia et al first and Reddivalla et al subsequently have demonstrated that LSM, using TE and two‐dimensional SWE, respectively, had a sudden increase up to more than a week before the diagnosis of VOD/SOS in pediatric patients. Recently, the same findings have been demonstrated in a monocentric cohort of 78 adult patients …”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…In addition, Colecchia et al first and Reddivalla et al subsequently have demonstrated that LSM, using TE and two‐dimensional SWE, respectively, had a sudden increase up to more than a week before the diagnosis of VOD/SOS in pediatric patients. Recently, the same findings have been demonstrated in a monocentric cohort of 78 adult patients …”
Section: Introductionsupporting
confidence: 79%
“…Although these three cases are homogenous in terms of transplant characteristics, they are not exhaustive and additional data are needed to confirm our observation that LSM may be a useful tool able to predict the clinical evolution of VOD under treatment, anticipating the improvement of clinical and laboratory signs of VOD/SOS. Furthermore, it would be really interesting to evaluate in pediatric patients the potential role of liver stiffness in the differential diagnosis between VOD/SOS and other hepatic complications (drug toxicity, acute GVHD), as recently evaluated in adults and to follow patients who did not have a good recovery after the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In HSCT patients, LSMs were carried out at baseline and once a week after HSCT. Only in patients who developed VOD/SOS, LSM values markedly increased compared to previous measurement (from 10.3-59.3 vs. 3.5-7.5 kPa) (62,63). Liver stiffness measurement increases from 1 to 15 days before clinical VOD/SOS diagnosis and most intriguingly LSM decreased after the start of defibrotide treatment parallel to clinical signs of VOD/SOS (e.g., bilirubin, weight) (63)(64)(65)(66)(67)(68)(69).…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 76%